41.2k views
4 votes
Find the value of the expression.
h(h + k)
for h = 4 and k = 6

2 Answers

3 votes

Answer:

40

Explanation:

We must substitute the values provided to us:


h=4 and
k=6

in the expression:


h(h+k)

we get the following:


4(4+6)

solving the sum inside the parentheses:


4(10)

and finally solving the multiplication


4(10)=40

the value of the expression is 40.

User Ubuntuuber
by
5.1k points
6 votes

Answer:

40

Explanation:

In this question, substitute the values of h and k in the expression

Given h=4 and k=6

The expression will be;

h(h+k)

4(4+6)

solve the brackets first

4+6=10

rewrite the expression as

4(10)

open the brackets by multiplication

4×10=40

User WooCaSh
by
4.9k points